Photo-realistic conversation agent - Zhang, Bo; Liu, Zicheng; Guo, Baining (Integrated image and graphics technologies, 2004)
Image-based facial animation (IBFA) techniques allow us to build photorealistic talking heads. In this chapter, we address two important issues in creating a conversation agent using IBFA. First, we show how to make a conversation agent appear to be alive during the conversation. Second, we present techniques for lip-syncing different languages in the same IBFA system. Using these techniques, we built two conversation agents, an English speaker and a Mandarin Chinese speaker, in our E-Partner system.We also present a geometry-driven facial expression synthesis system, which is very important to make talking head more naturally in the future. Given the feature point positions (geometry) of a facial expression, our system automatically synthesizes the corresponding expression image which has photo-realistic and natural looking expression details. This technique can be used to enhance the traditional expression mapping technique, or let user edit facial expression directly by moving feature points in our expression editing system.